The use of premature chromosome condensation to study in interphase cells the influence of environmental factors on human genetic material - Vasiliki I. Hatzi; Georgia I. Terzoudi; Christina Paraskevopoulou; Vasilios Makropoulos; Demetrios P. Matthopoulos; Gabriel E. Pantelias (The Scientific World Journal)
Nowadays, there is a constantly increasing concern regarding the mutagenic and carcinogenic potential of a variety of harmful environmental factors to which humans are exposed in their natural and anthropogenic environment. These factors exert their hazardous potential in humans' personal (diet, smoking, pharmaceuticals, cosmetics) and occupational environment that constitute part of the anthropogenic environment. It is well known that genetic damage due to these factors has dramatic implications for human health. Since most of the environmental genotoxic factors induce arrest or delay in cell cycle progression, the conventional analysis of chromosomes at metaphase may underestimate their genotoxic potential. Premature Chromosome Condensation (PCC) induced either by means of cell fusion or specific chemicals, enables the microscopic visualization of interphase chromosomes whose morphology depends on the cell cycle stage, as well as the analysis of structural and numerical aberrations at the G1 and G2 phases of the cell cycle. The PCC has been successfully used in problems involving cell cycle analysis, diagnosis and prognosis of human leukaemia, assessment of interphase chromosome malformations resulting from exposure to radiation or chemicals, as well as elucidation of the mechanisms underlying the conversion of DNA damage into chromosomal damage. In this report, particular emphasis is given to the advantages of the PCC methodology used as an alternative to conventional metaphase analysis in answering questions in the fields of radiobiology, biological dosimetry, toxicogenetics, clinical cytogenetics and experimental therapeutics.